Ohybová tuhost zubu čepovce po přední fixaci jedním tahovým šroubem - biomechanická studie - Buchvald, Pavel; Čapek, Lukáš; Barsa, Pavel (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2015)
PURPOSE OF THE STUDY The aim of the experiment was to compare the bending stiffness of an intact odontoid process with bending stiffness after its simulated type II fracture was fixed with a single lag screw. The experiment was done with a desire to answer the question of whether a single osteosynthetic screw is sufficient for good fixation of a type II odontoid fracture. MATERIAL AND METHODS The C2 vertebrae of six cadavers were used. With simultaneous measurement of odontoid bending stiffness, the occurrence of a fracture (type IIA, Grauer's modification of the Anderson- D'Alonzo classification) was simulated using action exerted by a tearing machine in the direction perpendicular to the odontoid axis. Each odontoid fracture was subsequently treated by direct osteosynthesis with a single lag screw inserted in the axial direction by a standard surgical procedure in order to provide conditions similar to those achieved by routine surgical management. The treated odontoid process was subsequently subjected to the same tearing machine loading as applied to it at the start of the experiment. The bending stiffness measured was then compared with that found before the fracture occurred. The results were statistically evaluated by the t-test for paired samples at the level of significance α = 0.05. RESULTS The average value of bending stiffness for odontoid processes of intact vertebrae at the moment of fracture occurrence was 318.3 N/mm. After single axial lag screw fixation of the fracture, the average bending stiffness for the odontoid processes treated was 331.3 N/mm. DISCUSSION Higher values of bending stiffness after screw fixation were found in all specimens and, in comparison with the values recorded before simulated fractures, the increase was statistically significant. CONCLUSIONS The results of our measurements suggest that the single lag screw fixation of a type IIA odontoid fracture will provide better stability for the fracture fragment-C2 body complex on antero-posterior perpendicular loading than can be found in intact C2 vertebrae. Key words: odontoid fracture, odontoid fixation, bending stiffness, lag screw.
Keywords: senioři; biomechanika; mrtvola; dens axis; Cadaver; Spinal Fractures; Biomechanical Phenomena; Middle Aged; mužské pohlaví; Fracture Fixation, Internal; Bone Screws; fraktury páteře; ženské pohlaví; Odontoid Process; Humans; vnitřní fixace fraktury; lidé středního věku; kostní šrouby; Female; Aged; lidé; Male